The scarcity of primary data in life cycle assessments of lithium-ion battery manufacturing: A systematic review - Jean C. Bassani,; Aglaer N. C. Leocadio,; Heverson R. de Freitas,; Marcell M. C. Maceno, (European Journal of Sustainable Development, 2025)
With increasing greenhouse gas emissions, lithium-ion batteries (LIBs) are becoming a promising technology for decarbonization, particularly in the urban mobility sector. However, their production involves critical materials and large energy consumption processes, requiring robust environmental evaluation. Life Cycle Assessment (LCA) plays a key role in assessing the environmental impacts of the manufacturing phase. This study presents a Systematic Literature Review (SLR) focused on identifying the use of primary data in LCAs of LIB manufacturing. The review was conducted using Scopus and SciFinder databases through an iterative search strategy combining keywords related to LIBs, manufacturing, LCA, and primary data. From an initial pool of over 205,000 articles, only four met the inclusion criteria of applying primary data to the manufacturing phase. Most studies focused on LMO and NMC chemistries, primarily in pouch or prismatic formats, and used cradle-to-gate boundaries. Despite being labeled as primary data based, these studies showed strong reliance on secondary datasets, limited geographical coverage, and no recent publications within the last five years. The variability in reported CO? emissions further reflects methodological inconsistencies. These findings indicate a literature gap in LCA studies using primary data for LIB manufacturing. Specifically, there is a lack of recent, geographically diverse, and methodologically transparent research, which raises concerns about the reliability of current environmental assessments. Keywords: Lithium- ion batteries, life cycle assessment, manufacture and primary data